Donut Dance Accounting - Dzurriyyatil Izzah; Irman Mamulati; Wirawati Abjan (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2025)
The donut dance phenomenon has become a global trend, as not just one creator account but dozens of accounts are dancing donuts with varying donut gift requirements. This community usually performs live, with some dancing alone, three or even six people, or in larger groups. This study is a qualitative study with a netnographic approach to understand how the donut dance accounting system implemented by the hosts so that many people are interested in dancing together. The results show that donut dance accounting contains conditions of meaning and value that are not just about money but more about the meaning of cooperation, self-identity, realistic expectations, economic orientation and social responsibility, all of which contain the values of togetherness, assets, existence, prosperity, family economic progress and the benefit of fellow villagers, then the donut dance accounting was formed.